What viruses tell us about evolution and immunity: beyond Darwin?. Issue 1 (29th April 2019) - Broecker, Felix; Moelling, Karin
Abstract: We describe mechanisms of genetic innovation mediated by viruses and related elements that, during evolution, caused major genetic changes beyond what was anticipated by Charles Darwin. Viruses and related elements introduced genetic information and have shaped the genomes and immune systems of all cellular life forms. None of these mechanisms contradict Darwin's theory of evolution but extend it by means of sequence information that has recently become available. Not only do small increments of genetic information contribute to evolution, but also do major events such as infection by viruses or bacteria, which can supply new genetic information to a host by horizontal gene transfer. Thereby, viruses and virus‐like elements act as major drivers of evolution. Abstract : Here, we describe mechanisms of genetic innovation mediated by viruses and related elements, which during evolution caused major genetic changes beyond what was anticipated by Charles Darwin.